Current practice of histopathology in Pakistan: difficulties, challenges, and solutions - Talat Zehra; Zubair Ahmed; Mahin Shams (Journal of the Pakistan Medical Association, 2023)
Histopathology is the gold standard for diagnosis of cancers as well as many non- neoplastic diseases. Pakistan is a country of more than 220 million people and the fifth most populated country of the world. Unfortunately, it has a weak healthcare system in general and poor pathology services in particular. Till date, only 338 histopathologists have passed their fellowship examination in Pakistan; this has led to a very alarming situation considering the marked increase in the prevalence of cancer cases and other diseases which need histopathological interpretation. There are only 18 big histopathological labs in the country, the majority of which are located in major cities which further delays the diagnosis of patients who live in rural areas. Immediate steps are required for better histopathology services in the country. Adoption of digital tools may bridge the gaps of histopathology-practice and ensure consistency across the country.